Persepsi Pelaku Umkm Batik Kabupaten Pekalongan Terhadap Financial Technology Syariah - Hidayatullah, Muhammad Syarif; Nassarrudin, Razie Bin; Mashudi, Mashudi (Department of Islamic Banking, Faculty of Islamic Economics and Business, Institut Agama Islam Negeri Pekalongan, 2021)
This study aims to determine and explain the perceptions of batik SMEs in the area of ​​wiradesa that are carried out in an effort to advance technology in this case is Islamic financial technology and explain how interested batik SMEs in the Wiradesa area are in conducting Islamic financing or peer to peer lending in sharia in Islamic financial technology. This research is a field research with a qualitative approach. To get valid data, the authors use data collection methods, namely interviews, documentation, and observation. There are two data sources in this study, namely primary data sources and secondary data sources. The results of this study stated that the perception of batik SMEs in the Wiradesa Region did not yet know or were unfamiliar with sharia financial technology and had an interest in participating in sharia financing in sharia financial technology on the grounds that sharia financing used sharia principles in the contract which made the SMEs of Batik feel not too anxious in running his business. And the SMEs of Batik in the Wiradesa Region also hope to hold a socialization about the use of services from Islamic financial technology providers to be able to understand the use of technology easily.